DYNAMICS OF THE LITHUANIAN PARLIAMENT’S LEGISLATIVE AGENDA DURING THE PERIOD OF 2005–2015 - Peciukonis, Vytautas; Antanavičius, Jonas; Drublionytė, Miglė; Grigaliūnaitė, Dovilė; Markevičiūtė, Anastazija; Nakrošis, Vitalis (Politologija, 2016)
Research based on agenda mapping and an analysis of the changing priority issues of governments is a new trend in the field of public policy analysis. Systematic indicators and universal codebooks have been developed in order to compare issue attention longitudinally, across decision-making venues and between countries. However, despite the increased interest in the subject internationally, this field of study has been neglected in Lithuania – no systematic longitudinal analysis of the Lithuanian political agenda has been conducted so far. Therefore, this article aims to fill the gap by analysing changes of the legislative agenda of the Lithuanian Parliament (Seimas).Data for the quantitative analysis was collected from the working programmes of 19 ordinary sessions of the Seimas between 2005 and 2015 and coded according to the Comparative Agendas Project’s Master Codebook. We sought to describe the general trends of the Parliament’s legislative agenda and to explain the main causes behind certain policy punctuations. We also analysed the EU’s influence on the Parliament’s agenda and the distribution of power between the legislative and the executive branches of power in formulating a list of priority legal acts. In order to answer these questions, six hypotheses were tested in our article.The results of our analysis revealed that the Lithuanian political agenda cannot be characterised as stable because a number of major agenda fluctuations occurred in the period between 2005 and 2015. Some of the policy punctuations coincided with elections as foreseen under the standard model, while other changes were disjoint and abrupt in line with the punctuated equilibrium theory. However, we observed incremental agenda changes in some, less politically sensitive, policy areas. Moreover, our research indicated the important role of external shocks – during the economic crisis political attention was allocated mostly to economy, taxes and public sector management, while the crisis in Ukraine increased focus on national defence issues. Finally, we found no evidence that the EU’s influence on the Lithuanian policy agenda is decreasing in the post-accession period. Taking the overload of the agenda of the Seimas into consideration, these punctuations reduce the ability of the legislature to adopt high quality legislation and to effectively solve public policy issues.